Clade C MERS-CoV camel strains vary in protease utilization during viral entry - Helena Winstone; Helen Stillwell; Li Hui Tan; Noam A. Cohen; Ranawaka A. P. M. Perera; Susan R. Weiss (Proceedings of the National Academy of Sciences, 2026)
Middle East Respiratory Syndrome coronavirus (MERS-CoV) is a lethal pathogen with pandemic potential. Clade A and B MERS-CoV viruses have caused outbreaks in the Middle East since 2012 when they initially spilled over from camels to humans. Clade C viruses, however, are only found in camels across Africa and the spillover potential of these viruses seems to be lower than for clade A/B strains but remains to be fully understood. Here, we report that clade C spikes are less well-cleaved at the S1/S2 boundary than clade A or B viral spikes and that most clade C spikes induce reduced syncytium formation. Additionally, we demonstrate that several East African clade C strains are less able to utilize the TMPRSS2-mediated pathway for viral entry in both cell lines and primary nasal epithelial cultures. We map the molecular basis of this reduced TMPRSS2 usage to the N-terminal domain and subdomain 2 of East African clade C MERS-CoV. We suggest that reduced usage of the TMPRSS2-mediated entry pathway may underlie the reduced replication of East African clade C strains in humans, while the reduced replication of West African strains remains to be further investigated. Altered protease usage may contribute to differential tropism of East African clade C strains and indicate geographically distinct selection pressures on spike between MERS-CoV strains circulating in camels.